Como a atividade cambial em plantas arbóreas do domínio semiárido responde aos fatores abióticos? - Silva, Andrieli Lima da (2023)
The growth of woody plants is divided into primary or axial (height) and secondary (increase in diameter). Secondary growth occurs through the activity of the cambium. The cell divisions of the cambium are related to vegetative and reproductive phenophases and to environmental factors (e.g. rainfall, temperature and photoperiod). In seasonally dry tropical environments, pulses of water interspersed with drought influence plant phenology and cambial activity. Understanding how cambial activity is regulated by phenology and environment is important for delineating the ecological response of plant growth in different environments. In seasonally dry tropical environments, secondary plant growth is expected to be synchronized with leaf life. However, this relationship is not yet well defined and may vary between species and environmental conditions. Moreover, information on cambial activity is scarcer for plants from seasonally dry tropical environments, such as the Brazilian semiarid. To discuss the latest advances regarding secondary growth in Seasonally Dry Tropical Forests, we conducted a literature review (Chapter 1). We found that water availability acts to increase cambium activity and water deficit, in general, leads to dormancy, but information on the action of other environmental factors on this meristem is scarce. To understand how secondary growth responds to environmental seasonality, we followed the cambial activity of species of the genus Cordia (Boraginaceae) for 12 months in seasonally dry environments with variations in water availability (Chapter 2). From measurements of cambial zone height, we estimated the effect of environmental variables on activity using a generalized linear mixed model (GLMM). Our results suggest that photoperiod is a trigger in activating cambial cell divisions under conditions of water availability and warmer temperatures. Our study has highlighted a more complex scenario for plant growth in a seasonally dry tropical environment.